2006
DOI: 10.1007/s00428-006-0240-3
|View full text |Cite
|
Sign up to set email alerts
|

Diminished expression of multidrug resistance-associated protein 1 (MRP1) in bronchial epithelium of COPD patients

Abstract: Cigarette smoke is the principal risk factor for chronic obstructive pulmonary disease (COPD). Multidrug resistance proteins, such as multidrug resistance-associated protein-1 (MRP1), P-glycoprotein (P-gp), and lung resistance-related protein (LRP), may protect against oxidative stress and toxic compounds generated by cigarette smoking. Expression of MRP1, P-gp, and LRP was evaluated in bronchial epithelium of two study groups of COPD patients and their controls and was associated with disease status and smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 21 publications
(22 reference statements)
5
49
1
1
Order By: Relevance
“…Functional inhalation studies would also provide an opportunity to demonstrate the effects of inhaled toxic substances, as postulated by van der Deen et al (31). Inhaled 99m Tc-sestamibi clearance is a functional imaging technique that was first described by Ruparelia et al in 2008 (25).…”
Section: Thoracic Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Functional inhalation studies would also provide an opportunity to demonstrate the effects of inhaled toxic substances, as postulated by van der Deen et al (31). Inhaled 99m Tc-sestamibi clearance is a functional imaging technique that was first described by Ruparelia et al in 2008 (25).…”
Section: Thoracic Imagingmentioning
confidence: 99%
“…They postulated that the delayed clearance of 99m Tc-sestamibi across the alveolocapillary barrier was regulated by active binding and efflux of Tcsestamibi by P-gp expressed in the lung tissue (26). They also postulated that delayed 99m Tc-sestamibi clearance in smokers compared with nonsmokers and protection against air pollution and inhaled toxic substances, such as those present in cigarette smoke (31). Indeed, Van der deen et al observed lower MRP1 expression in patients with chronic airway disease and postulated that the lower expression of MRP1 or the down-regulation of MRP1 may result in an increased vulnerability to, and subsequent development of, chronic airway disease (31).…”
Section: Thoracic Imagingmentioning
confidence: 99%
“…200,201 Moreover, it has been reported that toxins released from microorganisms infecting patients with cystic fibrosis also inhibit P-glycoprotein. 202 In patients with chronic obstructive pulmonary disease (COPD), there are no s ignificant data indicating modification of P-glycoprotein between the disease stages, 203,204 and no relevant data exist for asthma patients. Corticosteroids administered by the inhaled, oral, and intraperitoneal routes upregulate the P-glycoprotein transporter.…”
Section: Drug Transporters Atp-binding Cassette Transportersmentioning
confidence: 99%
“…203,211 It has been previously shown that smoking downregulates the transporter, and the transporter has a protective role against cell damage. 203,213 Ipratropium, N-acetylcysteine, and budesonide stimulate MRP 1 efflux and activity. 214 Formoterol in combination with budesonide reduces transporter activity, but formoterol on its own does not have an effect on the transporter.…”
Section: Drug Transporters Atp-binding Cassette Transportersmentioning
confidence: 99%
“…In the study performed by van der Deen et al, MDR proteins exhibited a protective effect against oxidative stress. It was found that COPD patients had a decreased level of MDR proteins in their bronchial epithelium 40 . Other authors have detected reduced P-gp expression and activity during inflammation 41 .…”
Section: Mdr1 and Copdmentioning
confidence: 99%